Proceedings of the 15th International Workshop on Data Management on New Hardware 2019
DOI: 10.1145/3329785.3329918
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Memory Allocation on High-Performance Query Processing

Abstract: Somewhat surprisingly, the behavior of analytical query engines is crucially affected by the dynamic memory allocator used. Memory allocators highly influence performance, scalability, memory efficiency and memory fairness to other processes. In this work, we provide the first comprehensive experimental analysis on the impact of memory allocation for high-performance query engines. We test five state-of-the-art dynamic memory allocators and discuss their strengths and weaknesses within our DBMS. The right allo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…This way, we can control the expected arrival rate of 𝜆 queries per second. This is similar to [2] -by not spacing the queries uniformly, we obtain dynamic workload fluctuations with bursts of queries arriving in short succession. To obtain a mixture of long and short running analytical requests, we sample from TPC-H queries at SF3 and SF30.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…This way, we can control the expected arrival rate of 𝜆 queries per second. This is similar to [2] -by not spacing the queries uniformly, we obtain dynamic workload fluctuations with bursts of queries arriving in short succession. To obtain a mixture of long and short running analytical requests, we sample from TPC-H queries at SF3 and SF30.…”
Section: Methodssupporting
confidence: 54%
“…In a more broad context, our work on scheduling falls into the important area of workload management within database systems. This is a wide ranging field incorporating topics like workload classification, admission control and resource management for memory and I/O [2,3,13,18,19].…”
Section: Related Workmentioning
confidence: 99%
“…Several prior studies have measured the effects of various basis factors on database performance. A recent study found that a good memory allocator alone can improve analytical query processing performance by 2.7Ă— [14]. A separate study presented a detailed evaluation of implementation and design choices in main-memory database systems, with a heavy focus on MVCC [55].…”
Section: Basis Factorsmentioning
confidence: 99%
“…Updating the metadata (e.g., bitmaps and logs) in the header space requires small writes to persistent memory. To study its access pattern, we profile the memory addresses of the first 1000 flush operations of metadata when running the DBMStest benchmark [16] using 4 allocators including nvm_malloc, PAllocator, PMDK, and Makalu. We show the results in Figure 2.…”
Section: Allocator-induced Small Random Accessmentioning
confidence: 99%